Influence of nutritional anemia on outcomes of colorectal cancer hospitalizations: a national inpatient sample database study - Changela, Madhav; Pandey, Sagar; Bahirwani, Janak; Patel, Nishit; Kaneriya, Maulik; Shah, Mihir; Basida, Sanket; Manvar, Kapilkumar; Adhikari, Samaj; Panigrahi, Kalpana (International Journal of Research in Medical Sciences, 2024)
Background: Colorectal carcinoma (CRC) is one of the leading causes of cancer related death globally. Prevalence of Nutritional Anemia is high among CRC patients. We aim to evaluate the role of Nutritional anemia on outcomes of CRC hospitalization. Methods: We conducted a retrospective cohort study using the Nationwide Inpatient Sample (NIS) database, including all adult CRC patients hospitalized in the United States from 2016 to 2019. Patients were stratified into those with and without nutritional anemia (16.19% vs 83.81%) which included iron, B12, folate deficiency and other nutritional anemia per ICD-10 coding. Mortality was the primary outcome whereas length of stay (LOS), total charges, acute kidney injury (AKI), pulmonary embolism (PE), deep vein thrombosis (DVT), colonoscopy, abdominal surgery and lower gastrointestinal (GI) bleeding were secondary outcomes. Multivariate regression model was used to estimate the outcomes of CRC hospitalization after adjusting for potential confounders. Results: A total of 504,515 patients were hospitalized for CRC. Among two groups, patients with anemia were older in age. Mortality was significantly lower among patients with nutritional anemia. Lower GI bleeding and colonoscopy during inpatient stay were significantly higher among CRC cohort with nutritional anemia. Similarly, LOS, total hospitalization charges, AKI, PE and DVT were also significantly higher among anemia cohort. However, need for abdominal surgery was significantly lower among CRC patients with nutritional anemia. Conclusions: Nutritional anemia in CRC patients is associated with longer length of stay, increased cost, higher risk of in-patient complications. Therefore, it should be corrected to optimize outcomes among CRC patients.